European Union's energy policy from the sustainability perspective - Henryk Manteuffel; Marcin Bukowski (Economic and Environmental Studies (E&ES), 2012)
In this article, the authors present their views on the main issues, objectives and measures in the EU energy policy in the context of increasing relative energy scarcity and sustainable development. Aims of sustainable access to energy seem to focus on increased access to fossil fuels, which may trade-off with the reduction of greenhouse gas emissions and hamper the development of renewable energy resources.
Keywords: 330; Foreign Direct Investment; EU energy policy; renewable energy sources; sustainable development